2017
DOI: 10.1016/j.bbmt.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Genetics on Outcome in Myelofibrosis Patients after Allogeneic Stem Cell Transplantation

Abstract: Molecular genetics may influence outcome for patients with myelofibrosis. To determine the impact of molecular genetics on outcome after allogeneic stem cell transplantation, we screened 169 patients with primary myelofibrosis (n = 110), post-essential thrombocythemia/polycythemia vera myelofibrosis (n = 46), and myelofibrosis in transformation (n = 13) for mutations in 16 frequently mutated genes. The most frequent mutation was JAK2V617F (n = 101), followed by ASXL1 (n = 49), calreticulin (n = 34), SRSF2 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 25 publications
10
82
2
1
Order By: Relevance
“…CALR mutations in PMF have also been shown to favorably affect spleen response and survival outcome in the setting of JAK2 inhibitor therapy . Consistent with the observations from the current study, triple‐negative mutational status did not affect post‐alloSCT outcome in a recent study of patients with primary or secondary myelofibrosis, where CALR mutations were associated with decreased non‐relapse mortality and increased overall and progression‐free survival; in the particular study, differences in outcome between type 1 and type 2 CALR mutations were not evident. Additional studies in both the transplant and nontransplant settings are needed to confirm the prognostically favorable impact of type 1/like CALR mutations in PMF, in the presence and absence of HMR mutations, and also in post‐ET MF, where recent studies have suggested a salutary effect for CALR mutations and a detrimental effect for triple‐negative mutational status …”
Section: Discussionsupporting
confidence: 88%
“…CALR mutations in PMF have also been shown to favorably affect spleen response and survival outcome in the setting of JAK2 inhibitor therapy . Consistent with the observations from the current study, triple‐negative mutational status did not affect post‐alloSCT outcome in a recent study of patients with primary or secondary myelofibrosis, where CALR mutations were associated with decreased non‐relapse mortality and increased overall and progression‐free survival; in the particular study, differences in outcome between type 1 and type 2 CALR mutations were not evident. Additional studies in both the transplant and nontransplant settings are needed to confirm the prognostically favorable impact of type 1/like CALR mutations in PMF, in the presence and absence of HMR mutations, and also in post‐ET MF, where recent studies have suggested a salutary effect for CALR mutations and a detrimental effect for triple‐negative mutational status …”
Section: Discussionsupporting
confidence: 88%
“…The observed mitigating effect of HCT on high risk and unfavorable karyotype was encouraging and underline the power of immunotherapy, as opposed to drug therapy alone, in eradicating cytogenetically aggressive clones in MF. Whether or not the same holds true for adverse mutations, as has been previously suggested for other chronic myeloid neoplasms, is currently under investigation and such information might also further clarify the interaction between DIPSS and transplant outcome. Finally, we recognize several limitations of the current study, including its retrospective design, relatively small sample size and the inclusion of post‐ET and post‐PV cases; the latter point was especially noteworthy considering the fact that our control group consisted entirely of patients with PMF and that both the revised cytogenetic risk stratification and DIPSS are based on PMF patients, although potentially applicable to secondary MF .…”
Section: Discussionmentioning
confidence: 63%
“…[14][15][16][17] A recent study about the outcome of 169 MF patients with different driver mutations reported 5y-OS and 5y-PFS of 56% and 48%, respectively. 18 In the cited study, only 4% of patients were MPL mut , 60% of them were Jak2 mut , 20%…”
Section: Discussionmentioning
confidence: 94%